DMS/O/P cycling during a marine heatwave in the NE subarctic Pacific (August 2022) ... - McNabb, Brandon; McCulloch, Ross; Peña, M. Angelica; Tortell, Philippe (SEANOE, 2025)
This dataset is associated with the article "Exceptionally high dimethyl sulfide concentrations during a marine heatwave in the NE subarctic Pacific". The data was collected in August 2022 as part of the long-term Line P time-series program in the NE subarctic Pacific. The primary data consists of underway-collected concentrations of DMS and DMSP along both the Line P transect and a northwards oceanic-coastal return transect. Time-course concentrations of unlabelled and isotopically-labelled (D3/D6/13C) DMSP, DMS and DMSO tracers, and the biological DMS/O/P turnover rates derived from them, are also provided for 4 incubation experiments conducted at the major Line P stations P4, P16, P20, and P26 (i.e. Ocean Station Papa). Additional ancillary data includes primary photosynthetic parameters (Fo, Fm, Fv) and maximum photosynthetic efficiency (Fv/Fm), HPLC pigment concentrations, and CHEMTAX input parameters and outputs used to derive the phytoplankton taxonomic composition along Line P. ...